TINJAUAN YURIDIS TERHADAP TANGGUNG JAWAB NOTARIS DALAM MEBUAT PPJB NOMOR 32 (STUDI PUTUSAN NOMOR ; 28/PDT.G/2015/PN.BGR) - Ling Fransiska; Endang Pandamdari (Jurnal Hukum Adigama, 2018)
Notary is a public official who makes an authentic Deed. In the implementation of the PPJB notary has fulfilled the legally binding of an agreement. However in the practice of making a PPJB Deed by a Notary List which is not based on existing facts, there has been no payment paid by the buyer but in PPJB the payment has been paid in full. The problem of this thesis is how the notary accountability in the making of PPJB no 32 (study decision number: 28 / PDT.G / 2015 / PN.BGR). The research method used is normative law research by using secondary data then analyzed qualitatively. The results of the investigation indicate that the Notary is negligent in making the deed so that the deed is degraded into a deed under the hand because the deed is assessed as having juridical defect and disadvantage one of the parties concerned. The notary may be liable for materially and materially in accordance with the law, UUJN and Code of Ethics.